Breakdown of immune homeostasis in the testis of mice lacking Tyro3, Axl and Mer receptor tyrosine kinases. Issue 6 (21st May 2013) - Zhang, Yue; Li, Nan; Chen, Qiaoyuan; Yan, Keqin; Liu, Zhenghui; Zhang, Xiaoyan; Liu, Peng; Chen, Yongmei; Han, Daishu
Abstract : Tyro3, Axl and Mer (TAM) receptor tyrosine kinases triple knockout (TAM −/− ) mice are male infertile due to impaired spermatogenesis. However, the mechanism by which TAM receptors regulate spermatogenesis remains unclear. In this study, we demonstrate that the testicular immune homeostasis was impaired in TAM −/− mice. As development after the onset of sexual maturity, germ cells were progressively degenerated. Macrophages and lymphocytes infiltrated into the testis as TAM −/− mice aged. Moreover, the integrity of blood–testis barrier was impaired, and the autoantibodies against germ cell antigens were produced. Major inflammatory cytokines, including tumor necrosis factor‐α, interleukin‐6 and monocyte chemotactic protein 1 were upregulated in the testis of TAM −/− mice, and predominantly located in Sertoli cells (SCs). In vitro assays showed that TAM −/− SCs secrete significantly high levels of inflammatory cytokines compared with wild‐type SCs after coculture with apoptotic germ cells. These results suggest that TAM receptors are important in the maintenance of the immune homeostasis in the testis.